Topographic influence on landslides characteristics and implication for risk management in upper Manafwa catchment, Mt Elgon Uganda - Nakileza, B. R; Nedala, S. (Springer International Publishing, 2020)
Abstract Abstract This study aimed to characterize the topographic effect on landslides attributes and explore the implications on risk management in a tropical mountainous environment. A database was constructed based on landslide inventory from field surveys supplemented by desk research. The topographic parameters were derived from STRM DEM of a 30 m resolution for the study area. The analysis of the data was conducted in Arc GIS 10.5 environment. The relationship between landslides and topographic conditioning factors was analysed using the Frequency Ratio model. Results revealed that most landslides were distributed within the altitudinal range of 1500 to 1800 m a.s.l. on moderately steep slopes (15 o-20o) in concave curvatures (hollows). Shallow slides mainly debris flows and debris slides were predominant. Most slope failures were initiated on mid to upper slope positions in either new or old scars. Some runout depositions of large slides ended in streams thus undermining water quality. The findings on topographic parameters have implications and yet landslide risk management by the local population was generally inadequate. Any efforts toward effective landslide risk management should prioritise greening the sensitive topographic hollows and old scars particularly on mid to upper slope positions.
Keywords: Landslides, Risk implications, Topographic parameters